Epidemiology of cercarial stage of trematodes in freshwater snails from Chiang Mai province, Thailand - Chontananarth T. (2014)
Objective: To investigate the epidemiological situation of cercarial trematodes infection in freshwater snails from different water resources in Chiang Mai province, Thailand. Methods: The snail specimens were collected from 13 districts of Chiang Mai province during April 2008 to February 2012. The prevalence of cercarial infection in snails was investigated using the crushing method. The drawing was done with the help of a camera lucida for the morphological study. Results: A total of 2 479 snail individuals were collected and classified into 7 families, 11 genera, and 14 species, Among them, 8 snails species were found to be infected with an overall prevalence of 17.27% (428/2 479), which infected with nine groups of cercariae; gymnocephalous cercaria, strigea cercaria, megalurous cercaria, monostome cercaria, parapleurolophocercous cercaria (Haplorchis cercaria), pleurolophocercous cercaria, furcocercous cercaria (Transversotrema cercaria), xiphidiocercaria, and virgulate cercaria. The parapleurolophocercous cercaria was found to be the dominant type among the cercarial infection in the snails (64.25%). Conclusions: The various species of snails found in the research location act as the intermediate hosts for the high prevalence of parasitic infection of many species of mammals. This work will provide new information on both the distribution and first intermediate host of trematodes. © 2013 Asian Pacific Tropical Biomedical Magazine.